2017
DOI: 10.1186/s12885-017-3463-6
|View full text |Cite
|
Sign up to set email alerts
|

UDP-glucuronosyltransferases and biochemical recurrence in prostate cancer progression

Abstract: BackgroundUridine 5′-diphosphate-glucuronosyltransferase 2B (UGT2B) genes code for enzymes that catalyze the clearance of testosterone, dihydrotestosterone (DHT), and DHT metabolites in the prostate basal and luminal tissue. The expression of the UGT2B15, UGT2B17, and UGT2B28 enzymes has not been evaluated in prostate tissue samples from hormone therapy-naïve patients.MethodsWe determined the expression of UGT2B15, UGT2B17, and UGT2B28 enzymes in 190 prostate tissue samples from surgical specimens of a multiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…17,29,31,33,50,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] The expression of UGTs is repressed in certain tumour types relative to their normal tissue counterparts, but remarkably enhanced in other cancers, such as those of the prostate, pancreas, lung, endometrium and in CLL, indicating diverse patterns of regulation of UGT expression in tumours. 17,29,31,33,50,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] These perturbed levels of UGTs are consistent with altered metabolic functions in tumours and suggest that UGTs might influence cancer progression, independent of exposure to therapeutic drugs (Table 1). Notably, in recent reports investigating metabolic perturbations present in the transcriptome and metabolome of multiple tumour types, 7...…”
Section: Ugts and Cancer Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,29,31,33,50,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] The expression of UGTs is repressed in certain tumour types relative to their normal tissue counterparts, but remarkably enhanced in other cancers, such as those of the prostate, pancreas, lung, endometrium and in CLL, indicating diverse patterns of regulation of UGT expression in tumours. 17,29,31,33,50,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] These perturbed levels of UGTs are consistent with altered metabolic functions in tumours and suggest that UGTs might influence cancer progression, independent of exposure to therapeutic drugs (Table 1). Notably, in recent reports investigating metabolic perturbations present in the transcriptome and metabolome of multiple tumour types, 7...…”
Section: Ugts and Cancer Progressionmentioning
confidence: 99%
“…4). 53,58,60,62,[75][76][77] A 2013 meta-analysis established that germline UGT2B17 deletion (inherited deficiency) is associated with an increased risk of prostate cancer. 78 Such data are lacking for the less common UGT2B28 deletion polymorphism.…”
Section: Ugt2b17mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that UGT is present in not only the liver, but also the small intestine, kidneys, brain, and esophagus [21, 22]. UGT2B is present in esophageal squamous cell carcinoma, with some recent reports indicating that it is related to prostate cancer and UGT2B genetic polymorphisms [23, 24]. Accordingly, genetic polymorphisms between UGT2B specimens might also be actively involved in the metabolism of carcinogens in the digestive tract.…”
Section: Discussionmentioning
confidence: 98%
“…Absence of UGT2B17 gene (CNV = 0) seems to increase the risk of cancer for prostate, breast, pancreatic, and lung cancer, but decreases the risk of colorectal cancer . On the other hand, overexpression of UGT2B17 protein has been linked to biochemical recurrence of prostate cancer, expedition in progression to castration‐resistant prostate cancer, and poorer prognosis in chronic lymphocytic leukemia due to inactivation of protective prostaglandin E 2 . Although presence of the UGT2B17 gene may be oncoprotective, its seemingly deleterious role in cancer progression suggests a separate function that is under differential regulation.…”
Section: Discussionmentioning
confidence: 99%